Печальный детектив: [повести, рассказы] / Виктор Астафьев - Астафьев Виктор Петрович (Сделано в СССР, 2015)
Экземпляры: аб. ЦБ (2016.12.13) / Инвентарный номер: 2607 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 91 / ГРНТИ: 17.82.31 / ББК: 84 (2 Рос=Рус)6